EMISSION ESTIMATION OF CARGO SHIPS ACCORDING TO SHIP MAIN DIMENSIONS AND ANNUAL EMISSON FOOTPRINT CALCULATION - Bilgili, Levent; Celebi, Ugur Bugra (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2015)
Shipbuilding industry is one of the oldest and most complex production and transportation methods. Merchant and military ships had significant importance throughout the history for both transportation of humans and goods. Due to its great carrying capacity, shipping is still the most important transportation method. Besides the uncountable benefits, ships have a considerable role on both human health and environment. Due to the combustion techniques, various operations and heavy fossil fuels, ships can produce remarkable amounts of solid, liquid and gaseous emissions. These emissions have serious effects on the environment, and it is predicted that the effects will increase in the near future. In order to prevent these effects, emission estimation techniques are very important. Through these methods, the emission amounts can be calculated, and thus, estimations for future can be realized. In this study, the harmful effects and previous studies on emission estimation methods are investigated. Using the annual cruise data, annual emission footprint is calculated of three different cargo ships. The emission density of the different routes is also calculated. Some formulas are obtained according to the estimation methods, characteristic principal dimensions of ships. These formulas can be used in order to estimate ships' emission footprints by using the information of ships' routes and main dimensions. The developed formulas provide estimation, even during the pre-design.
Keywords: Ship emissions; Life cycle assessment; Emission estimation; Ship emission footprint; TURBINE COMBINED CYCLES; UPDATED EMISSIONS; PRIME MOVERS; IMPACT; GAS; SIMULATIONS; PARAMETERS; INVENTORY; AEROSOLS; SYSTEM; Environmental Sciences & Ecology